Metal‐Free Aryl Cross‐Coupling Directed by Traceless Linkers - Haensch, Veit G. (John Wiley and Sons Inc., 2019)

(untitled) (Chemistry)
The metal‐free, highly selective synthesis of biaryls poses a major challenge in organic synthesis. The scope and mechanism of a promising new approach to (hetero)biaryls by the photochemical fusion of aryl substituents tethered to a traceless sulfonamide linker (photosplicing) are reported. Interrogating photosplicing with varying reaction conditions and comparison of diverse synthetic probes (40 examples, including a suite of heterocycles) showed that the reaction has a surprisingly broad scope and involves neither metals nor radicals. Quantum chemical calculations revealed that the C−C bond is formed by an intramolecular photochemical process that involves an excited singlet state and traversal of a five‐membered transition state, and thus consistent ipso–ipso coupling results. These results demonstrate that photosplicing is a unique aryl cross‐coupling method in the excited state that can be applied to synthesize a broad range of biaryls.